2003
DOI: 10.1177/01655515030293004
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying `ba': An Investigation of the Variables that are Pertinent to Knowledge Creation

Abstract: A comprehensive and feasible model that delineates the interrelationships among diversified learning mechanisms, information management and knowledge creation is absent. This study aims to fill this void. Unlike previous research, this study investigates the causality of knowledge creation from two different perspectives: information management strategy, i.e. distributed data application and administration (DDAA), and organizational learning mechanisms (OLM). A term has been defined, OIM (organizational inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
(76 reference statements)
0
20
0
1
Order By: Relevance
“…It's important to bear in mind that IT is only an enabler and not an end in itself. Here's a summary of tools, systems and applications cited in our analysis along with a few suggestions on the way they can be effectively applied: internet, intranet, yellow pages, business information systems, groupware, databases, datawarehousing, datamining, document repositories, software agents, repositories of information, best practices and lessons learned (von Krogh et al, 1997(von Krogh et al, ,2000Alavi and Leidner, 2001;Sabherwal and Becerra-Fernandez 2003;Chou and Wang, 2003;Lee and Choi, 2003); information systems designed to support collaboration, coordination and communication processes as a mean to facilitate teamwork and increase an individual's contacts with other individuals (Alavi and Leidner, 2001); e-mails and group support system in order to to increase the number of weak ties in organizations (Alavi and Leidner, 2001;Chou and Wang, 2003); computer simulation and smart software tutors to support individual learning in intranet environments (Alavi and Leidner, 2001;Tee, 2005); computer-mediated communication as a way to increase the quality of knowledge creation by enabling a forum for constructing and sharing beliefs, for confirming consensual information and for allowing expressing of new ideas (Alavi and Leidner, 2001); problem-solving systems based on a technology like casebased reasoning (Sabherwal and Becerra-Fernandez, 2003); virtual communities of practice (Pam and Leidner, 2003;Alvarenga Neto, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It's important to bear in mind that IT is only an enabler and not an end in itself. Here's a summary of tools, systems and applications cited in our analysis along with a few suggestions on the way they can be effectively applied: internet, intranet, yellow pages, business information systems, groupware, databases, datawarehousing, datamining, document repositories, software agents, repositories of information, best practices and lessons learned (von Krogh et al, 1997(von Krogh et al, ,2000Alavi and Leidner, 2001;Sabherwal and Becerra-Fernandez 2003;Chou and Wang, 2003;Lee and Choi, 2003); information systems designed to support collaboration, coordination and communication processes as a mean to facilitate teamwork and increase an individual's contacts with other individuals (Alavi and Leidner, 2001); e-mails and group support system in order to to increase the number of weak ties in organizations (Alavi and Leidner, 2001;Chou and Wang, 2003); computer simulation and smart software tutors to support individual learning in intranet environments (Alavi and Leidner, 2001;Tee, 2005); computer-mediated communication as a way to increase the quality of knowledge creation by enabling a forum for constructing and sharing beliefs, for confirming consensual information and for allowing expressing of new ideas (Alavi and Leidner, 2001); problem-solving systems based on a technology like casebased reasoning (Sabherwal and Becerra-Fernandez, 2003); virtual communities of practice (Pam and Leidner, 2003;Alvarenga Neto, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Deste modo, o conhecimento nasce da subjetividade de cada indivíduo, inserido num contexto com o encontro da objetividade através de processos sociais de trocas de informações, ou seja, é a interação do conhecimento tácito de cada indivíduo (subjetivo) com o conhecimento explícito (objetivo) e, juntos, são fontes para a criação de conhecimento (ALAVI; LEIDNER, 2001; NONAKA; TOYAMA; HIRATA, 2011). É através da distribuição de informação, ou o fluxo de informação, que o conhecimento é adquirido (ALLEN, 1977;HUBER, 1991;CHOU;WANG, 2003).…”
Section: Marco Teóricounclassified
“…In addition, studies have shown that organizational culture could have an impact on the performance of knowledge creation (Tushman and The current issue and full text archive of this journal is available at www.emeraldinsight.com/ 0025-1747.htm Which mode is better? O'Reilly, 1997;Mauriel et al, 2000;Martins and Terblanche, 2003;Chou and Wang, 2003). In general, the nature of organizational culture tends to lead to regulative behaviors that individuals or groups should obey.…”
Section: Introductionmentioning
confidence: 99%